Análisis de la participación de la mujer en informática - Rodríguez, Rocío Andrea (2017)
This article presents a study about women’s participation in the computing area, based on Argentinian universities. This was done by analyzing the percentage of women that hold positions of authorities in universities, as well as in the faculty (department or dependency) where computer engineering careers are given. This will allow to see the level of women’s participation in positions where important decisions are made. Moreover, master and doctoral thesis in the computing field are surveyed, being able to analyze the participation of women not only as thesis writers, but also as thesis directors, along the years. The data used to make these statistics was gathered from public information that those institutions have on their websites.